Effects of Elevated Temperature on Resources Competition of Nutrient and Light Between Benthic and Planktonic Algae - Mei, Xueying; Gao, Shanshan; Liu, Yang; Hu, Jie; Razlustkij, Vladimir; Rudstam, Lars G.; Jeppesen, Erik; Liu, Zhengwen; Zhang, Xiufeng (Frontiers in Environmental Science, 2022)
Climate warming, a serious environmental problem worldwide, is considered a major threat to aquatic ecosystems. A primary feature of climate warming is elevated temperatures which in shallow aquatic ecosystems might affect competition for light and nutrient between benthicand planktonic algae. The outcomes of such competition would not only affect the distribution of primary production, but also determine the fundamental character of shallow aquatic habitats as clear water or turbid water systems. We conducted a mesocosm study to evaluate the effects of elevated temperature on competition between planktonic algae and benthic algae for light and nutrients. We found that elevated temperature increased the concentrations of total nitrogen (TN), total phosphorus (TP), and total suspended solids (TSS) in overlying water and enhanced the growth of planktonic algae (measured as chlorophyll a, Chl a), but decreased light intensity and benthic algal biomass (Chl a). Our results indicate that elevated temperature can increase the growth of planktonic algae and enhance their competitive advantage over the benthic algae in shallow lakes, thereby contributing to eutrophication and a decline in water quality. These findings shed further light on the effects of global warming on aquatic ecosystems.